EFFECT OF DIETARY INCLUSION OF SOLVENT EXTRACTED AND DETOXIFIED KARANJ (PONGAMIA GLABRA VENT) CAKE ON COMMERCIAL LAYER PERFORMANCE - M.V.L.N.RAJU, RAJESH BABU, KRISHNA DAIDA, RAVINDER REDDY, NALINI KUMARI and (The Journal of Research, PJTSAU, 2019)
Karanj cake is rich in protein and was advocated for incorporation in various types of poultry rations at very low levels partially replacing soyabean meal (Krishna Daida, 2013). However, the feeding value of karanj cake on poultry is limited due to presence of toxic principles i.e. karanjin furanoflavonoid, tannins, trypsin inhibitor (Natanam et al. 1989). Recent study revealed that alkali treatment with NaOH or Ca(OH)2 of karanj cake reduced the karanjin content substantially. Present study was conducted to see the effect of dietary incorporation of solvent extracted karanj cake and detoxified karanj cake on body weight, body weight gain, feed consumption, hen day egg production, FCR (Feed intake/egg mass), feed intake per dozen eggs and egg mass per bird.